2011
DOI: 10.2147/vhrm.s16340
|View full text |Cite
|
Sign up to set email alerts
|

Effects on cardiovascular disease risk of a web-based health risk assessment with tailored health advice: a follow-up study

Abstract: Introduction:A large proportion of the cardiovascular disease (CVD) burden can potentially be prevented by primary prevention programs addressing major causal risk factors. A Web-based health risk assessment (HRA) with tailored feedback for individual health promotion is a promising strategy. We evaluated the effect on CVD risk of such a program among employees of a Dutch worksite.Methods:We conducted a prospective follow-up study among 368 employees who voluntarily participated in a Web-based HRA program at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 32 publications
1
32
0
2
Order By: Relevance
“…These results were consistent with the study by Colkesen et al [26] in that a 2 cm reduction in waist circumference was observed with no change in BMI over a 7-month period.…”
Section: Discussionsupporting
confidence: 93%
“…These results were consistent with the study by Colkesen et al [26] in that a 2 cm reduction in waist circumference was observed with no change in BMI over a 7-month period.…”
Section: Discussionsupporting
confidence: 93%
“…Within this stepwise approach (one invitation by regular mail, with two reminders, and only a box with additional measurements for the increased risk population) the dropout percentage is relatively high. Although the dropout rate is comparable to studies in an occupational health setting, 3,4 we think optimization of follow-up response of the 'at risk' population is mandatory for improving overall effectiveness of the programme. In focus group research citizens of Leidsche Rijn stated that they prefer measurements immediately at the start of an HRA 32 and in the practice.…”
Section: The Role Of the General Practitionermentioning
confidence: 84%
“…1 By addressing preventable risk factors, including high blood pressure, hypercholesterolaemia, hyperglycaemia, smoking, physical inactivity, stress and overweight, the CVD disease burden can be significantly decreased. [2][3][4] Many individuals are unaware of their risk of cardiovascular diseases and diabetes and, worldwide, health systems are struggling to determine the best ways for primary care and public health to collaborate in the implementation of effective prevention strategies. 5,6 Patients with coronary and vascular disease require a modern preventive cardiology programme to achieve healthier lifestyles, better risk factor control and, when needed, adherence to cardioprotective medications.…”
Section: Introductionmentioning
confidence: 99%
“…In 1 Dutch company, 368 employees volunteered to complete an internet-based health screening that included an evaluation of height, weight, waist circumference, blood pressure, a blood collection to determine lipids and glucose, and a urine sample for albumin and creatinine. 28 Employees were offered a health counseling session and tailored motivational and educational health advice. There was a significant improvement in the Framingham Risk Score (−4.9%, P=0.02) and even more substantial improvements among employees who were at the highest risk at baseline; among the 21 employees whose baseline Framingham Risk Score was ≥20%, CVD risk declined by 17.9% (P<0.001).…”
Section: Review Of Available Evidence Related To Workite Health Scrementioning
confidence: 99%